Recent advances in nutritional composition, phytochemistry, bioactive, and potential applications of Syzygium aromaticum L. (Myrtaceae) - Xue, Qing; Xiang, Zedong; Wang, Shengguang; Cong, Zhufeng; Gao, Peng; Liu, Xiaonan (Frontiers in Nutrition, 2022)
Syzygium aromaticum is an aromatic plant native to Indonesia, and introduced to tropical regions worldwide. As an ingredient in perfumes, lotions, and food preservation, it is widely used in the food and cosmetic industries. Also, it is used to treat toothache, ulcers, type 2 diabetes, etc. A variety of nutrients such as amino acids, proteins, fatty acids, and vitamins are found in S. aromaticum. In addition to eugenol, isoeugenol, eugenol acetate, β-caryophyllene and α-humulene are the main chemical constituents. The chemical constituents of S. aromaticum exhibit a wide range of bioactivities, such as antioxidant, antitumor, hypoglycemic, immunomodulatory, analgesic, neuroprotective, anti-obesity, antiulcer, etc. This review aims to comprehend the information on its taxonomy and botany, nutritional composition, chemical composition, bioactivities and their mechanisms, toxicity, and potential applications. This review will be a comprehensive scientific resource for those interested in pursuing further research to explore its value in food.